Recent developments in thin film (nano)composite membranes for solvent resistant nanofiltration - Hermans, Sanne; Mariën, Hanne; Van Goethem, Cedric; Vankelecom, Ivo FJ (Current opinion in chemical engineering, 2015)
•Diverse polymeric materials can be used for membrane separations in organic solvents.•A thin selective layer is beneficial for obtaining high solvent permeances.•The incorporation of fillers can increase membrane performance and stability. By separating organic mixtures at a molecular level, solvent resistant nanofiltration is offering a sustainable and reliable solution to many separation challenges in modern process industry. As solvent permeance is usually inversely proportional to the thickness of the selective layer, so-called thin film composite membranes offer great potential. They consist of a thin polymeric top-layer on a support which is generally prepared from another type of polymer. Excellent combinations of retention and permeance have been achieved by the most recent developments in this field. The incorporation of fillers, for example metal organic frameworks, in the top-layers has the potential to even further enhance the membrane performances. These solvent resistant nanofiltration membranes in general are expected to play an important role in the future industrial separation of solutes from organic streams.